KOMUNIKASI PERSUASIF HUMAS PT TUNGGAL PERKASA PLANTATION DALAM MENYELESAIKAN KONFLIK SENGKETA LAHAN DI KECAMATAN PASIR PENYU INDRAGIRI HULU - Indra, Budi; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Conflict land dispute between PT Tunggal Perkasa Plantation with the local community triggered by the expiration of the permit Hak Guna Usaha (HGU) plantation area of PT TPP since 2010. The fact that the company extended the concession of land up to 25 years. Furthermore, the Society requires companies to establish plantations of 20% of the total land area cultivated for the local community enterprise pursuant to Regulation No. 6 of 2007. PR of PT TPP seeks to resolve the conflict with the approach of persuasive communication. Thus, this study aims to determine (1) how the process of persuasive communication by PR PT TPP and (2) how persuasive communication techniques by PR PT TPP.This study uses a qualitative method and uses the concepts of persuasive communication. The subjects in this study amounted to 5 persons consisting of 1 PR / CDO (Community Development Officer) PT Tunggal Perkasa Plantation, two community leaders involved in persuasive communication, two community leaders to take action prosecution land. Subjects selected by using purposive technique. Data collected by interview, observation and documentation.The results of the studies showed that; (1) The process of persuasive communication done by Public Relations of PT TPP involve community leaders as a source. Recipients of persuasive communication is the local community that demands plantations partnership by doing blockade and taked over the land . Channel used in conveying the message is informal channels with the situation face to face and formal channel through the media. Feedback and effects of persuasive communication by Public Relations of PT TPP is the mass resignation and blockade against the company discontinued so that the company can re-work as usual. (2) Persuasive Communication Messages are delivered using the techniques of persuasive communication techniques including; inquire and express, take advantage of the situation, expressed consent to and sustainable approach.Keywords: Persuasif Communication, Public Relations, Local Communitiy